THE ORIGINS OF THE IDEA OF ESTABLISHING A â€œZIONIST CLIENT-STATEâ€ IN ISLAMICJERUSALEM - El-Awaisi, Khalid (Journal of Al-Tamaddun, 2019)
The idea of bringing the Jews to the region of Islamicjerusalem (the Holy Land) and establishing an entity for them preceded the creation of Zionism. The idea stemmed officially during the failed attempt of Napoleon to occupy the Holy Land. His campaign instigated British interest mingled with the idea of the â€œRestorationâ€ of Jews to Palestine as a prelude to the Second Coming of the Messiah. With the establishment of a British consulate in Jerusalem in 1838, Britain consolidated its influence and penetration of the region. The paper illustrates how the British were successful in fostering their colonial interest in the region through establishing a buffer state in Palestine against rival influences and later a Zionist Client-State that would continue to serve western interest in the region.